Surface morphology and structural modification induced by femtosecond pulses in hydrogenated amorphous silicon films - Almeida, G. F. B.; Cardoso, M. R.; Aoki, P. H. B. [UNESP]; Lima, J. J. D.; Costa, L. da F.; Rodrigues, C. A.; Constantino, C. J. L. [UNESP]; Mendonca, C. R. (Amer Scientific Publishers, 2015)
This work investigates the modification, resulting from fs-laser irradiation (150 fs, 775 nm and 1 kHz), on the structure and surface morphology of hydrogenated amorphous silicon (a-Si:H) thin films. The sample morphology was studied by performing a statistical analyzes of atomic force microscopy images, using a specially developed software that identifies and characterizes the domains (spikes) produced by the laser irradiation. For a fluence of 3.1 MJ/m(2), we observed formation of spikes with smaller average height distribution, centered at around 15 nm, while for fluencies higher than 3.7 MJ/m(2) aggregation of the produced spikes dominates the sample morphology. On the other hand, Raman spectroscopy revealed that a higher crystalline fraction (73%) is obtained for higher fluences (>3.1 MJ/m(2)), which is accompanied by a decrease in the size of the produced crystals. Therefore, such results indicate that there is a trade-off between the spike distribution, crystallization fraction and size of the nanocrystals attained by laser irradiation, which has to be taken into account when using such approach for the development of devices.
Keywords: Micromachining; Femtosecond pulses; Amorphous silicon; Surface morphology